A temperature-insensitive process corner detection circuit based on self-timing ring oscillator. (November 2022) - Yang, Lixin; Li, Dejian; Yang, Xiaokun; Feng, Xi; Tan, Lang; Shen, Chongfei; Cai, Hao
Abstract: A process corner detection circuit based on a self-timing ring oscillator is proposed to identify on-chip process variations. Composed of a self-timing ring oscillator with 5 stages of C-element, a counting module and a reset module, it is able to distinguish slow, typical and fast dies. Implemented in a 40 nm CMOS process with 1.2 V supply and 100 MHz frequency, it has a small area of 436 μm 2 with 0.18 mW power consumption. Implemented in the foundry's test circuit and tested with probe card in foundry, the measured results show that it can distinguish slow, typical and fast chips with no overlaps between the counting results under different temperatures of −25, 25, 75 and 125 °C. It is advantageous in its insensitivity to temperature for on-chip process corner detection. Highlights: An on-chip, all-digital circuit to detect discrete process corner (slow, typical and fast) Insensitive to temperature variation A compact structure with a very small area and power Fabricated in a 40 nm CMOS process and directly tested in the foundry